Search for events with large missing transverse momentum, jets, and at least two tau leptons in 7 TeV proton-proton collision data with the ATLAS detector* - Aad, Georges; Anders, Christoph; Anders, Gabriel; Andrei, George Victor; Davygora, Yuriy; Dietzsch, Thorsten; Geweniger, Christoph; Hanke, Paul; Henke, Michael; Kasieczka, Gregor; Khomich, Andrei; Kluge, Eike-Erik; et al. (Physics letters, 2012)
A search for events with large missing transverse momentum, jets, and at least two tau leptons has been performed using 2 fb−1 of proton-proton collision data at s=7 TeV recorded with the ATLAS detector at the Large Hadron Collider. No excess above the Standard Model background expectation is observed and a 95% CL upper limit on the visible cross section for new phenomena is set, where the visible cross section is defined by the product of cross section, branching fraction, detector acceptance and event selection efficiency. A 95% CL lower limit of 32 TeV is set on the gauge-mediated supersymmetry breaking (GMSB) scale Λ independent of tanβ. These limits provide the most stringent tests to date in a large part of the considered parameter space.